Community action in the paleontological resources of Pehuen Có, Buenos Aires (Argentina) (PAMPA, 2023)
Tourism is often an opportunity to promote local development of territories, producing processes of patrimonialization and valuation of resources. Around the paleontological resources of Pehuen Có, territorial processes have developed that reflect diverse interests and asymmetric relations of power and where the local community is fundamental in promoting patrimonialization through actions guided by the principles of the logic of gift, in experiences of the Social and Solidarity Economy. Thus, the aforementioned have been activated as tourist attractions and recognized as heritage. The objective of the research is to analyze a concrete action carried out by residents of Pehuen Có, in order to contribute to the value of their paleontological resources. Methodologically, a bibliographical review of the relationship between the logic of gift, social capital, the Social and Solidarity Economy and the processes of patrimonialization is proposed. Then we work with primary information obtained from an interview and analyze the socio-ecological conditions of the territory through a characterization of it with data collected in a field work.
Keywords: Reciprocity; Logic of gift; Paleontological heritage